Carbon risk and green transition: evidence from China - Li, Junfu; Xie, Yanxiang; Gao, Xiang; Wei, Qian (Frontiers in Public Health, 2024)
This paper thoroughly investigates the impact of carbon risk on the transition towards sustainability using data from Chinese manufactural companies listed for the period 2011-2020. There is strong evidence manifesting that the effect of carbon risk on corporate green transition is positive and statistically significant. The green transition is marked by the overall encouragement of exploratory, exploitable, autonomous, and collaborative green innovation. The mechanism test indicates that the enhancement of internal production structure and the pressure of external stakeholders are two fundamental pathways by which carbon risk influences the green transition. Additional examination reveals that the beneficial impact is particularly noticeable for companies that have limited capital intensity, minimal governmental assistance, reduced financial limitations, and are state-owned enterprises. These results are robust to resolve the problem of endogeneity by means of instrumental variables, Heckman two-step, placebo test, propensity score matching and difference-in-difference ways. Against the background of carbon neutrality, it is of great significance to examine the relationship between carbon risk and corporate green transition. The conclusion complements the knowledge of carbon risk and green transition, as well as provide theoretical reference and practical enlightenment for the green transition of manufacturing enterprises in emerging markets.